Mapping the landscape and evidence of cross-sectoral collaboration models targeting individuals referred for assessment of attention-deficit hyperactivity disorder or autism spectrum disorder: protocol for a scoping review - Niels Bilenberg; Pernille Tanggaard Andersen; Rikke Kirstine Kristensen; Emilie Dalsgaard Milling; Julie Dalgaard Guldager (BMJ Open)
Introduction Neurodevelopmental disorders, notably attention-deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD), present substantial challenges in mental health. Individuals referred for assessment in a psychiatric unit experience complex needs. This implies that their needs necessitate coordination across multiple sectors. Cross-sectoral collaboration models have emerged as essential strategies for addressing the complexities of these disorders. However, evidence of their existence, implementation and success remains limited. This protocol aims to outline a scoping review where we will explore existing collaboration models, evaluate their implementation and gain an understanding of how cross-sectoral collaboration models can be developed to ultimately benefit individuals referred for assessment of ADHD or ASD.Methods and analysis This proposed scoping review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines. A comprehensive search will be conducted across PubMed, CINAHL, Embase, PsycINFO and Google Scholar, as well as grey literature sources, between 1 December 2024 and 1 January 2025. Inclusion criteria will encompass studies focusing on cross-sectoral collaboration for individuals referred for assessment of ADHD or ASD, published in English, Danish, Norwegian or Swedish. The search will use a three-block search string, with iterative refinement guided by familiarity with the evidence base. Data extraction will involve study characteristics and implementation details, using the Consolidated Framework for Implementation Research in combination with Proctor et al’s implementation outcomes framework. Results will be synthesised into descriptive tables, providing a comprehensive mapping of existing models and emphasising implementation feasibility.Ethics and dissemination Ethical approval is not required for this protocol since it involves the review of existing literature without the involvement of human participants or personal data. Findings will be disseminated at national and international conferences and will be integrated into future efforts to develop cross-sectoral collaboration models in Denmark.